2019
DOI: 10.1002/acn3.50872
|View full text |Cite|
|
Sign up to set email alerts
|

Serum neurofilament light chain levels associations with gray matter pathology: a 5‐year longitudinal study

Abstract: Background Gray matter (GM) pathology is closely associated with physical and cognitive impairment in persons with multiple sclerosis (PwMS). Similarly, serum neurofilament light chain (sNfL) levels are related to MS disease activity and progression. Objectives To assess the cross–sectional and longitudinal associations between sNfL and MRI–derived lesion and brain volume outcomes in PwMS and age–matched healthy controls (HCs). Materials and Methods Forty‐seven HCs and 120 PwMS were followed over 5 years. All … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
62
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 73 publications
(77 citation statements)
references
References 44 publications
(55 reference statements)
7
62
1
Order By: Relevance
“…Our findings of associations between NfL levels and baseline reduction of BGM are corroborated by recent findings based on serum NfL. 26 Other studies reported relations between NfL in CSF or serum with longitudinal brain volume changes. 7 , 8 …”
Section: Discussionsupporting
confidence: 91%
“…Our findings of associations between NfL levels and baseline reduction of BGM are corroborated by recent findings based on serum NfL. 26 Other studies reported relations between NfL in CSF or serum with longitudinal brain volume changes. 7 , 8 …”
Section: Discussionsupporting
confidence: 91%
“…However, sNfL levels are generally considered to be biomarkers with a relatively short temporal window in which changes relate to the acute state of axonal damage [5]. Conversely to our hypoperfusion association, these acute MS changes, commonly seen as contrast-enhancing MS lesions, are accompanied by inflammation-induced hyperperfusion [7]. Regardless of the proposed directionality in the casual relationship between hypoperfusion and sNfL levels, we demonstrated that both changes in perfusion and neurodegeneration may describe overlapping MS pathophysiological mechanisms.…”
Section: Discussioncontrasting
confidence: 55%
“…However, with the development of fourth-generation single-cell array assays, such as Simoa, it is possible to measure concentrations in serum (sNfL). As such, sNfL has been utilized in various MS studies and successfully verified as a reliable proxy of axonal neuroinflammatory and neurodegenerative pathology [7].…”
Section: Introductionmentioning
confidence: 99%
“…10 In MS, elevated levels of serum neurofilament light have been shown to correlate with disease activity 11 and worse long-term clinical and paraclinical outcomes. 7,[11][12][13][14][15][16][17][18][19][20][21] Although these studies demonstrate utility for serum neurofilament light level as a potential biomarker associated with disease activity and shorter-term prognosis, information is scarce on the association of serum neurofilament light level at first MS presentation with long-term disease outcomes.…”
Section: Introductionmentioning
confidence: 99%